Adsorpsi Kromium Heksavalen Pada Larutan Aqueous Menggunakan Arang Kayu Teraktivasi Asam: Studi Isotherm Dan Kinetika - Afandy, Moh. Azhar; Sawali, Fikrah Dian Indrawati (Jurnal Ilmiah Teknik Kimia, 2024)
This research aims to carry out the adsorption process of hexavalent chromium Cr (VI) utilizing activated charcoal generated from acid-activated wood charcoal using HCl and evaluate the adsorption isotherm and kinetics model. The adsorption procedure was carried out in batches with variations in the Cr (VI) adsorbate concentration, and then the total concentration was finally evaluated using UV-VIS spectrophotometry. The isotherm models employed in this research include the Langmuir, Freundlich, and Temkin isotherm models, while the kinetic models used include pseudo-first order, pseudo-second order, Elovich, and Weber-Morris intraparticle diffusion, which may be estimated using linear regression equations. The findings obtained demonstrate that the adsorption capacity value of acid-activated wood charcoal is 1.1686 mg/g, with the greatest efficiency at 83.9623%. The isotherm model parameters found demonstrate that the Langmuir isotherm model is more acceptable for application in this research with values of R2 = 0.9956, qmax = 1.5126 mg/g, and KL = 0.0783 L/g. The Cr (VI) adsorption kinetics model employing acid-activated wood charcoal follows the pseudo-second-order kinetic equation with values of k2 = 0.0162 g/mg/minute, qe = 0.7927 mg/g, and R2 = 0.9543.